Wet felt and its preparation method and application
By using wet felt, combining water-soluble phenolic resin, surfactant, dispersant and polyacrylonitrile fibers, the problem of thermal conductivity paths of existing insulation felts during high-temperature heating is solved, achieving more efficient heating and more stable Insulation performance.
Patent Information
- Application Number
- CN202411563805.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-05
AI Technical Summary
During the high-temperature heating process, the existing insulation felt forms a thermal conductivity path due to the long fiber wire forming a heat transfer path, which affects the heating efficiency, the quality and production capacity of semiconductor silicon wafers.
Wet felts are used, including water-soluble phenolic resins, surfactants, dispersants and polyacrylonitrile fibers. Through specific volume ratios and preparation methods, materials with consistent density and low thermal conductivity are formed to avoid the formation of thermal conductivity paths.
It significantly improves heating efficiency, reduces energy consumption, enhances thermal insulation performance and thermal shock resistance, extends the service life of the material, simplifies the production process, and reduces costs.
Smart Images

Figure CN119061723B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal insulation materials, and in particular to a wet felt and a preparation method and application thereof. Background Art
[0002] Carbon fiber has become an indispensable material in many industries due to its excellent mechanical properties, high specific modulus, high specific strength, low thermal expansion coefficient and good toughness. These characteristics make carbon fiber widely used in many fields such as biology, chemical industry, automobile, machinery, aviation, aerospace, etc.
[0003] In the production process of semiconductor silicon wafers, resistance heating is used for the growth of single crystal silicon. Induction heating is used to heat silicon wafers in a vacuum environment. This method can provide fast and uniform heating and can be performed in the absence of oxygen, thus avoiding oxidation. This heating method is suitable for certain production steps of semiconductor silicon wafers that need to be performed in an oxygen-free or low-oxygen environment, such as annealing of silicon wafers. And in the heat treatment process of silicon wafers, such as oxidation, annealing or diffusion, inert gas furnaces are used to create a stable non-oxidizing environment to prevent oxidation of silicon wafers at high temperatures.
[0004] In these high-temperature processes, the use of thermal insulation materials is critical. They can reduce heat loss, improve energy efficiency, and maintain uniform temperature in the furnace. However, the raw materials of the current multi-purpose insulation felt are long fiber filaments, which lead to the formation of channels inside the insulation felt during the heating process, affecting the heating efficiency, and thus affecting the quality and production capacity of semiconductor silicon wafers.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One of the purposes of the present invention is to provide a wet felt, aiming to solve at least one of the above-mentioned technical problems in the prior art.
[0007] A second object of the present invention is to provide a method for preparing a wet felt.
[0008] The third object of the present invention is to provide an application of a wet felt.
[0009] In order to solve the above-mentioned technical problems, the present invention particularly adopts the following technical solutions:
[0010] A first aspect of the present invention provides a wet-laid felt comprising a water-soluble phenolic resin, a surfactant, a dispersant and polyacrylonitrile fibers.
[0011] Furthermore, the volume ratio of the water-soluble phenolic resin, the surfactant and the dispersant is 50:5-20:1-5, preferably 50:10-15:2-3.
[0012] Preferably, the volume mass ratio of the water-soluble phenolic resin to the polyacrylonitrile fiber is 50:2-8, preferably 50:4-6.
[0013] Furthermore, the length of the polyacrylonitrile fiber is 1 to 10 mm, preferably 2 to 6 mm.
[0014] Preferably, the surfactant includes at least one of polysorbate, sodium stearate, sodium dodecylbenzene sulfonate, glyceryl monostearate, lauryl alcohol polyoxyethylene ether, oleyl alcohol polyoxyethylene ether, palmitol polyoxyethylene ether, stearyl alcohol polyoxyethylene ether, cyclohexanol polyoxyethylene ether, terpene alcohol polyoxyethylene ether, alkyl glucoside, fatty acid glyceride, fatty acid sorbitan, polysorbate, fatty acid polyoxyethylene ester, polyoxyethylene alkylamine and polyoxyethylene alkylolamide, preferably polysorbate and sodium dodecylbenzene sulfonate.
[0015] Preferably, the dispersant comprises at least one of styrene-acrylate copolymer, polypropylene pyrrolidone, polyacrylamide, N-vinyl pyrrolidone copolymer and butadiene-acrylonitrile copolymer, preferably polyacrylamide.
[0016] Furthermore, the density of the wet felt is 0.16-0.18 g / cm 3 , thermal conductivity ≤0.172W / (m·K).
[0017] The second aspect of the present invention provides a method for preparing the wet felt, comprising the following steps:
[0018] A. adding an aqueous solution of a water-soluble phenolic resin into a mixed solution made of a surfactant and a dispersant and stirring the mixture to obtain a water-soluble phenolic resin dispersion;
[0019] B. adding polyacrylonitrile fiber to the water-soluble phenolic resin dispersion and mixing them evenly to obtain a slurry;
[0020] C. removing liquid from the slurry to form a wet felt sample, compressing, curing and subjecting the wet felt sample to high-temperature heat treatment to obtain the wet felt.
[0021] Furthermore, in the aqueous solution of the water-soluble phenolic resin, the volume proportion of the water-soluble phenolic resin is 20-30%, preferably 23-26%.
[0022] Preferably, the liquid in the slurry is removed by suction filtration.
[0023] Preferably, the suction filtration is performed using a water circulation mixer.
[0024] Preferably, the pressure of the water circulating mixer to filter the solution is 0.2-0.4 MPa.
[0025] Further, the compressing and the curing are performed in a hot press.
[0026] Preferably, the compression ratio of the compression is 80-90%.
[0027] Preferably, the heating temperature of the hot press is 80-120° C., and the heating time is 1-3 hours.
[0028] Preferably, the curing temperature is 180-220° C. and the curing time is 2-6 hours.
[0029] Furthermore, the wet felt sample is placed in a hot press, heated to 100° C. while being pressurized, and kept warm for 2 hours to compress the wet felt sample to 85% of its original volume, and then kept warm at 200° C. for 4 hours for the curing.
[0030] Preferably, the liquid obtained by filtration is returned to step B for recycling.
[0031] Furthermore, the high temperature heat treatment is performed in an argon atmosphere.
[0032] Preferably, the temperature of the high temperature heat treatment is 2000-2200°C.
[0033] The third aspect of the present invention provides the use of the wet-laid felt in a semiconductor thermal field.
[0034] Compared with the prior art, the present invention has at least the following beneficial effects:
[0035] In the wet-laid felt provided by the present invention, the polyacrylonitrile fibers are interlaced, loose and disordered throughout the wet-laid felt, which makes the heat transfer path tortuous, thereby reducing the thermal conductivity of the material. In addition, the wet-laid felt of the present invention has a highly consistent density ranging from 0.16 to 0.18 g / cm³. This consistency of density ensures that there is no difference in the thermal insulation performance of the material in different areas, further enhancing the overall thermal insulation effect. In addition to the structural advantages, the wet-laid felt of the present invention also has the characteristic of low thermal conductivity, which enables the material to better maintain its thermal insulation performance in high temperature environments. At the same time, the material exhibits excellent thermal shock resistance and corrosion resistance, which enable the wet-laid felt to remain stable in extreme temperature changes and chemical corrosion environments, thereby extending the service life of the material. Polyacrylonitrile fiber as a raw material not only avoids the formation of a heat conduction path in the wet-laid felt itself, but also has excellent thermal insulation performance and high temperature resistance.
[0036] The preparation method of the wet-laid felt provided by the present invention is simple to operate, has a continuous process, is highly controllable, is easy to realize industrialized production, improves production efficiency, reduces production costs, and makes the production of the wet-laid felt more economical.
[0037] The application of the wet felt provided by the present invention, in view of the above-mentioned advantages of the wet felt, makes the wet felt an ideal thermal insulation material in the production process of semiconductor silicon wafers, especially in high-temperature environments such as resistance heating, induction heating vacuum furnaces and inert gas furnaces. It can significantly improve the heating efficiency while reducing energy consumption, bringing significant energy efficiency improvements to the semiconductor production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0039] Figure 1 This is a scanning electron microscope image of the wet felt provided in Example 1. DETAILED DESCRIPTION
[0040] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution in the embodiment of the present invention will be clearly and completely described below in combination with the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, but not all of the embodiments. The components of the embodiment of the present invention can be arranged and designed in various different configurations.
[0041] A first aspect of the present invention provides a wet-laid felt comprising a water-soluble phenolic resin, a surfactant, a dispersant and polyacrylonitrile fibers.
[0042] In the wet-laid felt provided by the present invention, the polyacrylonitrile fibers are interlaced, loose and disordered throughout the wet-laid felt, which makes the heat transfer path tortuous, thereby reducing the thermal conductivity of the material. In addition, the wet-laid felt of the present invention has a highly consistent density ranging from 0.16 to 0.18 g / cm³. This consistency of density ensures that there is no difference in the thermal insulation performance of the material in different areas, further enhancing the overall thermal insulation effect. In addition to the structural advantages, the wet-laid felt of the present invention also has the characteristic of low thermal conductivity, which enables the material to better maintain its thermal insulation performance in high temperature environments. At the same time, the material exhibits excellent thermal shock resistance and corrosion resistance, which enable the wet-laid felt to remain stable in extreme temperature changes and chemical corrosion environments, thereby extending the service life of the material. Polyacrylonitrile fiber as a raw material not only avoids the formation of a heat conduction path in the wet-laid felt itself, but also has excellent thermal insulation performance and high temperature resistance.
[0043] The advantage of water-soluble phenolic resin as a resin for wet felt is that it can provide excellent thermal and chemical stability. In high-temperature environments such as semiconductor thermal fields, this resin can withstand extreme temperature conditions without decomposition or performance degradation, thereby ensuring the long-term use and reliability of wet felt. In addition, the chemical corrosion resistance of water-soluble phenolic resin enables it to maintain its performance in various chemical environments, preventing the wet felt from rapid aging or damage under chemical erosion. The high cross-linking density of phenolic resin also gives the wet felt excellent mechanical properties, including good tensile strength and impact resistance, so that the felt material exhibits better durability and deformation resistance under physical stress. At the same time, the molding and processing performance of water-soluble phenolic resin is good, which is convenient for forming a uniform and dense structure through a wet process, which helps to improve the overall performance and application effect of the wet felt.
[0044] At the same time, water-soluble phenolic resin does not need to use organic solvents during the dispersion process, but uses water as a solvent, which greatly reduces the emission of volatile organic compounds (VOC), thereby reducing pollution to the environment and potential threats to the health of operators. In addition, since organic solvents are usually expensive, using water as a solvent can significantly reduce the cost of raw materials and improve the economy of the production process.
[0045] Surfactants reduce the surface tension of the aqueous solution, promote the uniform dispersion of the water-soluble phenolic resin in water, and form a stable water-soluble phenolic resin dispersion. This uniform dispersion state is the basis for the subsequent preparation of high-quality wet felt.
[0046] At the same time, the surfactant improves the compatibility between polyacrylonitrile fiber and phenolic resin, allowing the fiber to be evenly dispersed in the resin dispersion to form a uniform slurry. This uniform mixing helps to achieve a good combination between the fiber and the resin.
[0047] In addition, the presence of surfactants helps to form a uniform cross-linked structure during the curing process of the wet felt sample, thereby improving the mechanical strength and thermal stability of the wet felt. During the preparation process, the surfactant can also reduce the shrinkage and deformation of the wet felt sample during the drying process, thereby ensuring the dimensional stability and shape consistency of the wet felt. These combined effects of the surfactant make the wet felt have better uniformity and fiber distribution, which helps to improve the mechanical properties and use effect of the final wet felt.
[0048] Dispersants ensure uniform distribution of fibers in phenolic resin by improving the dispersibility of fibers in the slurry. This uniform distribution is essential for forming a wet-laid felt with uniform structure and stable performance. The addition of dispersants reduces the tendency of fibers to aggregate and prevents the formation of fiber bundles, thereby improving the physical properties of wet-laid felt, such as strength and flexibility. In addition, dispersants also help improve the fluidity of the slurry. During the beating process, the addition of dispersants makes the fibers smaller and more evenly distributed, which helps to improve the strength and flexibility of the fibers. At the same time, the addition of dispersants also helps to improve the dispersion of fibers in the suspension.
[0049] In the preparation process of wet-laid felt, the addition of dispersants can also help improve production efficiency. By reducing fiber aggregation, dispersants can reduce blockage and wear problems in the production process, thereby increasing the speed and stability of the production line. In addition, the addition of dispersants can also improve the surface quality of wet-laid felt, reduce defects, and improve product consistency and reliability.
[0050] Furthermore, the volume ratio of the water-soluble phenolic resin, the surfactant and the dispersant is 50:5-20:1-5, preferably 50:10-15:2-3.
[0051] Typically but not limiting, the volume ratio of the water-soluble phenolic resin, the surfactant and the dispersant can be 50:5:1, 50:10:1, 50:15:1, 50:20:1, 50:5:2, 50:10:2, 50:15:2, 50:20:2, 50:5:3, 50:10:3, 50:15:3 or 50:20:3, or any volume ratio within the range of 50:5~20:1~5; in some preferred embodiments of the present invention, the volume ratio of the water-soluble phenolic resin, the surfactant and the dispersant can be 50:10:2, 50:15:2, 50:20:2, 50:10:3, 50:15:3, 50:20:3, or any volume ratio within the range of 50:10~15:2~3.
[0052] Preferably, the volume mass ratio of the water-soluble phenolic resin to the polyacrylonitrile fiber is 50:2-8, preferably 50:4-6.
[0053] Typically but not limiting, the volume mass ratio of the water-soluble phenolic resin to the polyacrylonitrile fiber can be 50:2, 50:3, 50:4, 50:5, 50:6, 50:7 or 50:8, or any value within the range of 50:2 to 8. The preferred volume mass ratio is as follows: 50:4, 50:5 or 50:6, or any value within the range of 50:4 to 6.
[0054] It should be noted that the above volume-to-mass ratio corresponds to the volume of the water-soluble phenolic resin and the mass of the polyacrylonitrile fiber.
[0055] Furthermore, the length of the polyacrylonitrile fiber is 1-10 mm, preferably 2-6 mm. Within this length range, the polyacrylonitrile fiber can be more evenly distributed, making the structure of the wet-laid felt denser, thereby improving its thermal insulation and tensile strength.
[0056] Typically, but not limiting, the length of the polyacrylonitrile fiber can be 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or 10 mm, or any value within the range of 1 to 10 mm. The preferred length can be 2 mm, 3 mm, 4 mm, 5 mm or 6 mm, or any value within the range of 2 to 6 mm.
[0057] Preferably, the surfactant includes at least one of polysorbate, sodium stearate, sodium dodecylbenzene sulfonate, glyceryl monostearate, lauryl alcohol polyoxyethylene ether, oleyl alcohol polyoxyethylene ether, palmitol polyoxyethylene ether, stearyl alcohol polyoxyethylene ether, cyclohexanol polyoxyethylene ether, terpene alcohol polyoxyethylene ether, alkyl glucoside, fatty acid glyceride, fatty acid sorbitan, polysorbate, fatty acid polyoxyethylene ester, polyoxyethylene alkylamine and polyoxyethylene alkylolamide, preferably polysorbate and sodium dodecylbenzene sulfonate.
[0058] Preferably, the dispersant comprises at least one of styrene-acrylate copolymer, polypropylene pyrrolidone, polyacrylamide, N-vinyl pyrrolidone copolymer and butadiene-acrylonitrile copolymer, preferably polyacrylamide.
[0059] Furthermore, the density of the wet felt is 0.16-0.18 g / cm 3 , thermal conductivity ≤0.172W / (m·K).
[0060] The second aspect of the present invention provides a method for preparing the wet felt, comprising the following steps:
[0061] A. adding an aqueous solution of a water-soluble phenolic resin into a mixed solution made of a surfactant and a dispersant and stirring the mixture to obtain a water-soluble phenolic resin dispersion;
[0062] B. adding polyacrylonitrile fiber to the water-soluble phenolic resin dispersion and mixing them evenly to obtain a slurry;
[0063] C. removing liquid from the slurry to form a wet felt sample, compressing, curing and subjecting the wet felt sample to high-temperature heat treatment to obtain the wet felt.
[0064] The preparation method of the wet-laid felt provided by the present invention is simple to operate, has a continuous process, is highly controllable, is easy to realize industrialized production, improves production efficiency, reduces production costs, and makes the production of the wet-laid felt more economical.
[0065] Furthermore, in the aqueous solution of the water-soluble phenolic resin, the volume proportion of the water-soluble phenolic resin is 20-30%, preferably 23-26%.
[0066] The volume proportion of water-soluble phenolic resin is 20-30%, which can ensure that the phenolic resin has good dispersion performance in the solution, thereby improving its bonding with materials such as fibers. When the volume proportion of water-soluble phenolic resin is within this range, it can form an effective cross-linked network between fibers, enhance the structural integrity of wet felt, and thus improve its stability and durability in high temperature environments. At the same time, the addition of an appropriate amount of resin can also optimize the molding process of wet felt, so that it can form a uniform network structure during the curing process, further improving the uniformity and overall performance of the material. The volume proportion of water-soluble phenolic resin is controlled at 20% to 30%, which can also ensure that the wet felt has good insulation performance and chemical corrosion resistance. This volume proportion of phenolic resin helps to form a uniform insulation layer in the wet felt, improve its electrical insulation performance, and reduce the risk of arcing and electrical breakdown. At the same time, the chemical stability of water-soluble phenolic resin can also enhance the chemical corrosion resistance of wet felt, so that it can maintain stable performance in a chemical corrosion environment.
[0067] Typically but not limiting, the volume proportion of the water-soluble phenolic resin in the aqueous solution of the water-soluble phenolic resin can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% or 30%, or any value in the range of 20% to 30%; preferably, the volume proportion can be 23%, 24%, 25% or 26%, or any value in the range of 23% to 26%.
[0068] Preferably, the liquid in the slurry is removed by suction filtration.
[0069] Preferably, the suction filtration is performed using a water circulation mixer.
[0070] Preferably, the pressure of the water circulating mixer to filter the solution is 0.2-0.4 MPa.
[0071] Typically but not limiting, the pressure of the filtered solution in the water circulation mixer can be 0.2 MPa, 0.25 MPa, 0.3 MPa, 0.35 MPa or 0.4 MPa, or any value within the range of 0.2-0.4 MPa.
[0072] Furthermore, the compression and curing are performed in a hot press, and a tighter bond is formed between the polyacrylonitrile fiber and the phenolic resin of the wet felt sample. By applying pressure, the phenolic resin flows and penetrates between the fibers at high temperature, promoting the cross-linking reaction of the phenolic resin. This process not only increases the density of the wet felt sample, but also enhances its mechanical strength and durability. At the same time, the temperature of the hot press causes the phenolic resin to be initially cured to generate a preliminary cross-linked network structure.
[0073] Preferably, the compression ratio of the compression is 80-90%.
[0074] Typically but not restrictively, the compression ratio of the compression may be 80%, 85%, 90%, or any value within the range of 80-90%.
[0075] Preferably, the heating temperature of the hot press is 80-120° C., and the heating time is 1-3 hours.
[0076] Typically but not limitatively, the heating temperature of the hot press can be 80°C, 90°C, 100°C, 110°C, 120°C, or any value within the range of 80-120°C; the hot pressing time can be 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours, or any value within the range of 1-3 hours.
[0077] Preferably, the curing temperature is 180-220° C. and the curing time is 2-6 hours.
[0078] Typically but not limiting, the curing temperature can be 180°C, 190°C, 200°C, 210°C, 220°C, or any value within the range of 180-220°C; the curing time can be 2 hours, 3 hours, 4 hours, 5 hours or 6 hours, or any value within the range of 2-6 hours.
[0079] Furthermore, the wet felt sample is placed in a hot press, heated to 100° C. while being pressurized, and kept warm for 2 hours to compress the wet felt sample to 85% of its original volume, and then kept warm at 200° C. for 4 hours for the curing.
[0080] Preferably, the liquid obtained by suction filtration is returned to step B for recycling. The liquid obtained by suction filtration is a water-soluble phenolic acid resin dispersion, which contains a surfactant, a dispersant, a water-soluble phenolic resin and water. Recycling the liquid can make full use of the above raw materials, thereby saving resources, and at the same time reduce the preparation cost of wet felt, reduce energy consumption and waste generation, and improve production efficiency.
[0081] Furthermore, the high temperature heat treatment is performed in an argon atmosphere.
[0082] Preferably, the temperature of the high temperature heat treatment is 2000-2200°C. After the high temperature heat treatment, the structure of the wet felt will be further optimized. Under high temperature conditions, the cross-linking degree of the phenolic resin increases, forming a more stable three-dimensional network structure. The formation of this structure helps to improve the thermal stability and thermal shock resistance of the wet felt. In addition, high temperature heat treatment may also cause the volatilization or decomposition of some organic components, thereby reducing impurities in the material and improving its purity and performance.
[0083] Typically but not limiting, the temperature of the high temperature heat treatment may be 2000°C, 2050°C, 2100°C, 2150°C or 2200°C, or any value within the range of 2000-2200°C.
[0084] The third aspect of the present invention provides the use of the wet-laid felt in a semiconductor thermal field.
[0085] The application of the wet felt provided by the present invention, in view of the above-mentioned advantages of the wet felt, makes the wet felt an ideal thermal insulation material in the production process of semiconductor silicon wafers, especially in high-temperature environments such as resistance heating, induction heating vacuum furnaces and inert gas furnaces. It can significantly improve the heating efficiency while reducing energy consumption, bringing significant energy efficiency improvements to the semiconductor production process.
[0086] In the following, some embodiments of the present invention are described in detail in conjunction with the examples. In the absence of conflict, the following examples and features in the examples can be combined with each other. The raw materials in the following examples and comparative examples are purchased from the market unless otherwise specified.
[0087] Example 1
[0088] This embodiment provides a wet felt, and the preparation method is as follows:
[0089] 1. Put 50 mL of polysorbate, 100 mL of sodium stearate, 100 mL of sodium dodecylbenzene sulfonate, and 50 mL of polyacrylamide into a beaker and mix them into a solution. Stir magnetically for 30 minutes to mix them into solution A.
[0090] 2. Take 1000mL of water-soluble phenolic resin and 4000mL of deionized water, stir and mix them evenly to form solution B.
[0091] 3. Pour solution A and solution B into an ultrasonic disperser and stir ultrasonically at 25°C for 30 minutes. Then take 100g of 3mm long polyacrylonitrile fiber chopped strands and stir ultrasonically at 25°C for 60 minutes to obtain a carbon fiber mixed solution C.
[0092] 4. Pour the mixed solution C into a water circulation mixer, filter out the solution under a pressure of 0.3 MPa, and form a wet felt-like embryo A on a stainless steel filter screen.
[0093] 5. Place the wet felt sample A into a hot press and compress it to 85%, keep it at 100°C for 2 hours, then heat it to 200°C and keep it for 4 hours to solidify, and finally obtain the wet felt sample B.
[0094] 6. Heat treat the wet felt sample B at 2100°C in an Ar atmosphere to obtain a wet felt.
[0095] Example 2
[0096] This embodiment provides a wet felt. The difference from Embodiment 1 is that in step 1, the amounts of polysorbate, sodium stearate, sodium dodecylbenzene sulfonate, and polyacrylamide are 40 mL, 80 mL, 80 mL, and 40 mL, respectively. The other steps are the same as those in Embodiment 1 and will not be repeated here.
[0097] Example 3
[0098] This embodiment provides a wet felt. The difference from Embodiment 1 is that in step 1, the amounts of polysorbate, sodium stearate, sodium dodecylbenzene sulfonate, and polyacrylamide are 60 mL, 100 mL, 100 mL, and 60 mL, respectively. The other steps are the same as those in Embodiment 1 and will not be repeated here.
[0099] Example 4
[0100] This embodiment provides a wet felt. The difference from Embodiment 1 is that in step 2, the amounts of water-soluble phenolic resin and deionized water are 500 mL and 2000 mL respectively. The other steps are the same as those in Embodiment 1 and will not be described again.
[0101] Example 5
[0102] This embodiment provides a wet felt. The difference from Embodiment 1 is that in step 2, the amounts of water-soluble phenolic resin and deionized water are 1500 mL and 6000 mL respectively. The other steps are the same as those in Embodiment 1 and will not be described again.
[0103] Example 6
[0104] This embodiment provides a wet felt. The difference from Embodiment 1 is that the amount of polyacrylonitrile fiber chopped strands added in step 3 is 80 g, the suction pressure of the water circulation mixer in step 4 is 0.2 MPa, and the other steps are the same as in Embodiment 1 and will not be repeated here.
[0105] Example 7
[0106] This embodiment provides a wet felt. The difference from Embodiment 1 is that the amount of polyacrylonitrile fiber chopped strands added in step 3 is 120 g, the suction pressure of the water circulation mixer in step 4 is 0.4 MPa, and the other steps are the same as in Embodiment 1 and will not be repeated here.
[0107] Example 8
[0108] This embodiment provides a wet felt, and the preparation method is as follows:
[0109] 1. Same as the step in Example 1.
[0110] 2. Same as the step in Example 1.
[0111] 3. Same as the step in Example 1.
[0112] 4. Same as the step in Example 1.
[0113] 5. Put the wet felt sample A into the hot press and compress it to 80%, keep it at 80℃ for 3 hours, then raise the temperature to 180℃, keep it at this temperature for 6 hours to solidify, and finally obtain the wet felt sample B.
[0114] 6. Heat treat the wet felt sample B at 2000°C in an Ar atmosphere to obtain a wet felt.
[0115] Example 9
[0116] This embodiment provides a wet felt, and the preparation method is as follows:
[0117] 1. Same as the step in Example 1.
[0118] 2. Same as the step in Example 1.
[0119] 3. Same as the step in Example 1.
[0120] 4. Same as the step in Example 1.
[0121] 5. Place the wet felt sample A into a hot press and compress it to 90%, keep it at 120°C for 1 hour, then heat it to 220°C, keep it at this temperature for 2 hours to solidify, and finally obtain the wet felt sample B.
[0122] 6. Heat treat the wet felt sample B at 2200°C in an Ar atmosphere to obtain a wet felt.
[0123] Example 10
[0124] This embodiment provides a wet felt, and the preparation method is as follows:
[0125] 1. The solution filtered out in Example 1 was recovered, and the mass of the solution filtered out was subtracted from the mass of the carbon filament mixed solution C to obtain a mass of 1060 g of the wet felt sample A.
[0126] 2. Re-mix 1060 g of the mixed solution, i.e., 10 mL, 20 mL, 20 mL, 10 mL of polysorbate, sodium stearate, sodium dodecylbenzene sulfonate, and polyacrylamide, 200 mL of water-soluble phenolic resin, and 800 mL of deionized water, and mix them with the filtered solution.
[0127] 3. Same as the step in Example 1.
[0128] 4. Same as the step in Example 1.
[0129] 5. Same as the step in Example 1.
[0130] 6. Same as the step in Example 1.
[0131] Characterization example
[0132] The wet felt obtained in Example 1 was subjected to a scanning electron microscope, and the results were as follows: Figure 1 shown.
[0133] from Figure 1 It can be seen that the polyacrylonitrile fibers are interlaced, loose and disordered, making the heat transfer path tortuous and reducing the thermal conductivity of the wet felt. The polyacrylonitrile fiber chopped strands are all chopped strands, which cannot form paths with each other, avoiding the self-ignition of the wet felt material, and can reduce the thermal conductivity of the wet felt and improve the thermal insulation; the horizontal and vertical distribution of the polyacrylonitrile fiber chopped strands are arranged without obvious directional differences, that is, there is no processing direction restriction for subsequent machining, easy to process, and has excellent assemblability.
[0134] Test Case
[0135] The wet felt obtained in the example was subjected to thermal conductivity test and thermal insulation test.
[0136] Thermal conductivity refers to the amount of heat transferred through an area of 1 square meter in 1 second when the temperature difference between the two surfaces of a 1 meter thick material is 1 degree (K, °C) under stable heat transfer conditions. It is expressed as λ and is expressed in watts / (meter·degree), w / (m·k) (W / m·K, K here can be replaced by ℃). Use DRPL-III thermal conductivity tester for testing.
[0137] Heat preservation: The heater was wrapped with a special semiconductor thermal field wet felt in the furnace, and the average temperature of the outer wall of the wet felt was measured in an Ar atmosphere. The thickness of the wet felt was 50 mm, and the heating rate of the heater was 20°C / min.
[0138] The obtained data are shown in Table 1 below.
[0139] Table 1
[0140]
[0141] As can be seen from Table 1, Example 1 has the best thermal insulation performance and high temperature resistance. When the heater is heated to 2000°C, the outer surface temperature of the wet felt is only 92.8°C. The amount of dispersant, resin, and fiber filaments used will have a direct impact on the density, thermal conductivity, thermal insulation performance, and high temperature resistance. The density and thermal conductivity of some embodiments are roughly the same as those of Example 1, and the thermal insulation performance at 500°C and 1000°C is excellent, but the high temperature resistance at 1500°C and 2000°C is reduced, and the thermal insulation performance drops sharply. By comparing Example 1 with Example 10, it can be seen that the solution filtered out by the water circulation mixer can be recycled, and the density, thermal conductivity, thermal insulation performance, and high temperature resistance of the prepared wet felt are still excellent.
[0142] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A wet felt, characterized in that: Density: 0.16~0.18g / cm 3 , thermal conductivity ≤ 0.172W / (m·K); The preparation method of the wet felt comprises the following steps: A. adding an aqueous solution of a water-soluble phenolic resin into a mixed solution made of a surfactant and a dispersant and stirring the mixture to obtain a water-soluble phenolic resin dispersion; B. adding polyacrylonitrile fiber to the water-soluble phenolic resin dispersion and mixing them evenly to obtain a slurry; C. removing liquid from the slurry to form a wet felt sample, compressing, curing and subjecting the wet felt sample to high-temperature heat treatment to obtain the wet felt; The high temperature heat treatment is carried out in an argon atmosphere; the temperature of the high temperature heat treatment is 2000-2200°C; The volume ratio of the water-soluble phenolic resin, the surfactant and the dispersant is 50:(5-20):(1-5); The volume mass ratio of the water-soluble phenolic resin to the polyacrylonitrile fiber is 50 mL: (2-8) g.
2. The wet-laid felt according to claim 1, characterized in that: The length of the polyacrylonitrile fiber is 1 to 10 mm; The surfactant comprises at least one of polysorbate, sodium stearate, sodium dodecylbenzene sulfonate, glyceryl monostearate, lauryl alcohol polyoxyethylene ether, oleyl alcohol polyoxyethylene ether, palmitol polyoxyethylene ether, stearyl alcohol polyoxyethylene ether, cyclohexanol polyoxyethylene ether, terpene alcohol polyoxyethylene ether, alkyl glucoside, fatty acid glyceride, fatty acid sorbitan, polysorbate, fatty acid polyoxyethylene ester, polyoxyethylene alkylamine and polyoxyethylene alkyl alcohol amide; The dispersant includes at least one of styrene-acrylate copolymer, polypropylene pyrrolidone, polyacrylamide, N-vinyl pyrrolidone copolymer and butadiene-acrylonitrile copolymer.
3. The wet-laid felt according to claim 1, characterized in that: In the aqueous solution of the water-soluble phenolic resin, the volume proportion of the water-soluble phenolic resin is 20-30%; Removing liquid from the slurry by suction filtration; A water circulation mixer is used to carry out the suction filtration; The pressure of the filtered solution of the water circulation mixer is 0.2~0.4MPa.
4. The wet-laid felt according to claim 1, characterized in that: performing said compressing and said curing in a hot press; The compression ratio of the compression is 80-90%; The heating temperature of the hot press is 80-120°C and the heating time is 1-3h; The curing temperature is 180-220° C. and the curing time is 2-6 hours.
5. The wet-laid felt according to claim 1, characterized in that: The wet felt sample is placed in a hot press, heated to 100° C. while being pressurized, and kept warm for 2 hours, the wet felt sample is compressed to 85% of the original volume, and then kept warm at 200° C. for 4 hours for curing; The liquid obtained by filtration is returned to step B for recycling.
6. Use of the wet-laid felt according to any one of claims 1 to 5 in a semiconductor thermal field.
Citation Information
Patent Citations
Method for processing wool short-fiber wet-formed felt
CN109024059A